Cobalt and magnesium ferrite nanoparticles: preparation using liquid foams as templates and their magnetic characteristics - Bala, Tanushree; Sankar, C. R.; Baidakova, Marina; Osipov, V.; Enoki, Toshiaki; Joy, Pattayil Alias; Bhagavatula L. V. Prasad; Sastry, M. (Langmuir, 2005)
An easy and convenient method for the synthesis of cobalt and magnesium ferrite nanoparticles is demonstrated using liquid foams as templates. The foam is formed from an aqueous mixture of an anionic surfactant and the desired metal ions, where the metal ions are electrostatically entrapped by the surfactant at the thin borders between the foam bubbles and their junctions. The hydrolysis is carried out using alkali resulting in the formation of desired nanoparticles, with the foam playing the role of a template. However, in the formation of ferrites with the formula MFe2O4, where the metal ion and iron possess oxidation states of +2 and +3, respectively, forming a foam from a 1:2 mixture of the desired ionic solutions would lead to a foam composition at variance with the original solution mixture because of greater electrostatic binding of ions possessing a greater charge with the surfactant. In our procedure, we circumvent this problem by preparing the foam from a 1:2 mixture of M2+ and Fe2+ ions and then utilizing the in situ conversion of Fe2+ to Fe3+ under basic conditions inside the foam matrix to get the desired composition of the metal ions with the required oxidation states. The fact that we could prepare both CoFe2O4 and MgFe2O4 particles shows the vast scope of this method for making even multicomponent oxides. The magnetic nanoparticles thus obtained exhibit a good crystalline nature and are characterized by superparamagnetic properties. The magnetic features observed for CoFe2O4 and MgFe2O4 nanoparticles are well in accordance with the expected behaviors, with CoFe2O4 particles showing higher blocking temperatures and larger coercivities. These features can easily be explained by the contribution of Co2+ sites to the magnetocrystalline anisotropy and the absence of the same from the Mg2+ ions.

Controlled aggregation of gold nanoparticle networks induced by alkali metal ions - Tamang, Sudarsan; Hotha, Srinivas; Bhagavatula L. V. Prasad (Journal of Nanoscience and Nanotechnology, 2007)
Gold nanoparticle networks were obtained by linking them with cysteine modified triethyleneglycols. The oligo-ether linker molecule initially having a linear structure probably adopts a crown ether type structure upon complexation with alkali metal ions that leads to a controlled aggregation of the network. The extent of aggregation depends on the degree of conformational change in the molecule upon complexation with the metal ion, which in turn is governed by the metal ion radius leading to a dependence of red shift of the surface plasmon resonance on the metal ion radius. Since this network is present in the organic solvent they also act as phase transferring agent for the alkali metal ions from aqueous to organic media.
Keywords: Aggregation; Alkali Metal Ions; Au Nanoparticles; Crown Ether; Surface Plasmon Resonance

Carbon nano horn and bovine serum albumin hierarchical composite: towards bio-friendly superhydrophobic protein film surfaces - Jadhav, Anil D.; Ogale, Satishchandra B.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2008)
Highly hydrophilic glass substrates when coated with films of carbon nano horns dispersed in the ubiquitous protein bovine serum albumin display hydrophobic characteristics. Incidentally both the materials used to create the final hydrophobic surface are known to be highly bio-compatible. The features observed are accredited to the replication of the micro and nanoscale hierarchical structures of carbon nano horns in the final film composite.

C-glycosides of dodecanoic acid: new capping/reducing agents for glyconanoparticle synthesis - Ramana, C. V.; Durugkar, Kulbhushan A.; Puranik, Vedavati G.; Narute, Sachin B.; Bhagavatula L. V. Prasad (Tetrahedron Letters, 2008)
A concise synthesis of 12-C-glycosylated dodecanoic acids employing an olefin cross-metathesis reaction is developed. Examination of these acids as capping agents for the synthesis of metal nanoparticles reveals that they do not cap the Co-metal nanoparticles synthesized in aqueous phase, but that two of them can reduce and cap the Ag nanoparticles in water without any aggregation. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: C-Glycosides; Cross metathesis; glyconanoparticles; Grubbs' catalyst; silver nanoparticles

Composites of plasma treated poly(etherimide) films with gold nanoparticles and lysine through layer by layer assembly: a ``friendly-rough'' surface for cell adhesion and proliferation for tissue engineering applications - D'Britto, Virginia; Tiwari, S.; Purohit, V.; Wadgaonkar, P. P.; Bhoraskar, S. V.; Bhonde, Ramesh R.; Bhagavatula L. V. Prasad (Journal of Materials Chemistry, 2009)
A composite film fabricated by plasma treated poly(etherimide) with subsequent deposition of gold nanoparticles and lysine using layer by layer assembly has been demonstrated to be good for cell attachment and proliferation making it an attractive strategy for tissue engineering applications. As compared to the other methods the decrease in contact angle obtained here does not depend much on the plasma treatment thus affecting the polymer structure minimally. A combination of surface roughness provided by the gold nanoparticles and the presence of amine groups of lysine is hypothesized to be the reason for the features observed.

Citrate-capped quantum dots of CdSe for the selective photometric detection of silver ions in aqueous solutions - Ingole, Pravin P.; Rajiv M. Abhyankar; Bhagavatula L. V. Prasad; Haram, Santosh K. (Materials Science and Engineering B-Advanced Functional Solid-State Materials, 2010)
A simple strategy for the synthesis of water soluble, luminescent, citrate-capped CdSe quantum dots (Q-CdSe) and their applications to selective detection of silver ions are described. The steady state photoluminescence (PL) spectra show single, narrow emission band at ca. 554 nm without any contribution from the trap states. The effect of various ions including physiologically important metal ions (viz. K(+), Ca(2+), Fe(3+), Zn(2+), Mg(2+), Mn(2+), Cu(2+), Ag(+), Pb(2+) and Cd(2+)), on the PL intensity of citrate-capped Q-CdSe has been studied. Among these, selective luminescence quenching with Ag(+) ion was found to be predominant. Under the optimum conditions, the response was linear between 1.7 and 18 mu M. The quenching constant K(SV) was found to be ca. 3.4 x 10(5) M(-1). The mechanism of photoluminescence quenching of Q-CdSe by metal ions (Ag(+)) is also discussed. Based on these studies, the potential use of Q-CdSe as a luminescent probe for the selective detection of silver ion has been proposed. (C) 2009 Elsevier B.V. All rights reserved.
Conference on Specialty Advanced Materials and Polymers for Aerospace and Defense and Applications (SAMPADA-2008), Mat Res Soc Singapore, Singapore, SINGAPORE, JUL 03-08, 2005
Keywords: Ag(+) ions; Luminescence quenching; Luminescent probe; Q-CdSe; Tri-sodium citrate

Clicking molecular hooks on silica nanoparticles to immobilize catalytically important metal complexes: the case of gold catalyst immobilization - Ganai, Anal Kumar; Bhardwaj, Rima; Hotha, Srinivas; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
Gold mediated reactions have emerged as one of the best choices for affecting a variety of chemical transformations with a wide range of functional group tolerance. Application of such transformations to industrial processes necessitates immobilization of the Au ions into a matrix for easy separation of the catalyst after reaction. We report the synthesis and characterization of silica nanoparticles in which Au(III) has been immobilized through a 1,2,3-triazole linkage using an alkynalated picolinic acid exploiting ``click chemistry''. The Au( III) immobilized silica nanoparticle has been thoroughly characterized using FT-IR, C-13 CP MAS NMR and XPS. The utility of these particles as an easily separable catalyst for the Hashmi phenol synthesis is also reported.

Continuous flow synthesis of functionalized silver nanoparticles using bifunctional biosurfactants - Kumar, D. V. Ravi; Kasture, Manasi; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad; Kulkarni, A. A. (Green Chemistry, 2010)
Silver nanoparticles were synthesized by continuous flow methods using biosurfactants, namely, oleic acid sophorolipid (OASL) and stearic acid sophorolipid (SASL). Both the sophorolipids can act as reducing and capping agents. The effect of temperature on the completion of nanoparticle formation and the particle growth dynamics (size) were studied in batch mode. While the completion of the reaction using oleic acid sophorolipid needed 20 min, only 5 min were required with the stearic acid sophorolipid as capping and reducing agent. Hence all the continuous flow experiments were carried out using the stearic acid sophorolipid. The continuous flow synthesis of silver nanoparticles was carried out in a stainless steel helical coil and also in a spiral polymeric minichannel reactor. The DLS results show that higher flow rate leads to the formation of bigger and polydisperse particles because of incomplete reactions. Higher residence time allowed the completion of reaction leading to spherical, small and monodisperse particles.

Cytotoxic and genotoxic assessment of glycolipid-reduced and -capped gold and silver nanoparticles - Singh, Sanjay; D'Britto, Virginia; Prabhune, Asmita; Ramana, C. V.; Dhawan, Alok; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2010)
A systematic cytotoxic and genotoxic evaluation of glycolipid-conjugated silver and gold nanoparticles is carried out. These glycolipid nanoparticle conjugates are obtained by exploiting the reductive capability of a class of glycolipids called sophorolipids that play the role of capping agent as well. Further, when tested for their cytotoxicity and genotoxicity on HepG2 cells, these nanoparticles are found to be cytocompatible up to 100 mu M metal concentrations. Of the two metallic systems investigated, gold nanoparticles are found to be more cytocompatible than the same concentrations of silver nanoparticles. Similarly, it is also demonstrated that at 100 mu M, silver nanoparticles cause more DNA damage compared to gold nanoparticles of similar concentrations.

Cytotoxicity of sophorolipid-gellan gum-gold nanoparticle conjugates and their doxorubicin loaded derivatives towards human glioma and human glioma stem cell lines - Dhar, Sheetal; Reddy, E. Maheswara; Prabhune, Asmita; Pokharkar, Varsha; Shiras, Anjali; Bhagavatula L. V. Prasad (Nanoscale, 2011)
Biocompatible gold nanoparticles were synthesized by using a naturally occurring gum-Gellan Gum-as a capping and reducing agent. These were further conjugated with sophorolipids which again were accessed through a biochemical transformation of a fatty acid. The cellular uptake of sophorolipid-conjugated gellan gum reduced gold nanoparticles and their cytotoxicity on human glioma cell line LN-229 and human glioma stem cell line HNGC-2 were investigated. Quite surprisingly even the simple sophorolipid-conjugated gellan gum reduced/capped gold nanoparticles showed greater efficacy in killing the glioma cell lines and, gratifyingly, the glioma stem cell lines also. The cytotoxic effects became more prominent once the anti cancer drug doxorubicin hydrochloride was also conjugated to these gold nanoparticles.